The Higa-unon Kutiapi: A Two-Stringed Plectrum Lute - Englis, Francisco A. (Silliman Journal, 2023)
On Mindanao Island, southern Philippines, numerous non-Muslim, non-Christian tribal groups—collectively categorized as the Mindanao lumad (tribes)—still perform their traditional music. These musical genres existed long before the advent of Islam in 1490 and Christianity in 1521 in the Philippines. This paper on the indigenous plectrum lute, the kutiapi, of one lumad, the Higa-unons of Rogongon, a barangay (village) in the City of Iligan, province of Lanao del Norte, documents one such oral tradition. The paper will present the findings of the study of Higa-unon kutiapi music, namely, its mythological evolutions, role in the society, repertoire and performance practice, and music making techniques. It will also include organological descriptions of the kutiapi as an instrument with a zoomorphic corpus. It is evident that the tribe's cultural heritage, if not already acculturated, is fast disappearing, Thus the study tried to find out what remained of the traditional kutiapi music and what the people still know about the origin of kutiapi. This was done through field investigation, interviews, audio documentation of actual kutiapi playing and qualitative description of the instrument, as well as observation and analysis of the socio-economic and political conditions obtaining in the community, which maybe factors for culture change. It is hoped that this presentation will provide the impetus for further research on Higa-unon music, especially in the areas of Higa-unon's preferences in the organization of their music, the identification of specific repertoire for other instruments, the kutiapi's possible 21st century transformations, and the possible transcription into notation of various archaic ritual songs.